Upaya Meningkatkan Pemahaman Guru tenteng Pendidikan Budaya dan Karakter Bangsa melalui Kegiatan Mgmp Sekolah di SMP Negeri 38 Pekanbaru - Sarinah Sarinah (Bedelau: Journal of Education and Learning, 2021)
This study aims of school action search to increase teachers understanding of cultural education and national character through school MGMP activities. School action research is carried out at SMP N 38 Pekanbaru, 2020. The research subject are 25 teachers. Data collection techniques are by concludting guidance on school MGMP activities. The research instrument is in the form of a test question. The discussion technique in this research is done descriptively, namely the data obtained are analyzed and then described in the form of sentences and conclusions are drawn. The pre-cycle is only 40 % which is categorized as suffient. In cycle 1 it increased by 70% in the good category. In cycle 2 it increased by 85% in the very goog category. MGMP activities can increase teachers’ understanding of cultural education and national character.